Intraamniotic digoxin administration versus intracardiac or funic potassium chloride administration to induce foetal demise before termination of pregnancy: a prospective study - Akalın, Münip; Demirci, Oya; Gokcer, Oya; İsmailov, Hayal; Sahap Odacilar, Ali; Dizdarogulları, Gizem Elif; Kahramanoğlu, Özge; Ocal, Aydın; Bolat, Guher; Eriç Özdemir, Mucize (Journal of obstetrics and gynaecology, 2022)
Different foeticide techniques and pharmacological agents have been used to achieve foetal asystole. This study aimed to compare the success of intraamniotic digoxin, intracardiac potassium chloride (KCl), and funic KCl in achieving foetal asystole and discuss procedural difficulties for physicians and clinical outcomes. This prospective observational study included 124 patients who received foeticide at 22-31 weeks of gestation. All procedures were performed transabdominally, and 1 mg of intraamniotic digoxin, funic KCl, or intracardiac KCl was administered. Procedure times, procedural difficulty scores, patient pain scores, decrease in haematocrit levels, induction and hospitalisation times, and the presence of chorioamnionitis were recorded. The foeticide success rates were 93.0, 95.1, and 97.5% for intraamniotic digoxin, intracardiac KCl, and funic KCl, respectively. Intraamniotic digoxin was associated with shorter procedure times, lower procedural difficulty scores, and lower patient pain scores ( < 0.001). Decreases in haematocrit, induction times, and chorioamnionitis were similar in all three procedures. Success rates and clinical results were similar for all three procedures. Foeticide with intra-amniotic digoxin has a high success rate, the procedure is easier to perform, and patients experience less procedural pain.IMPACT STATEMENT Different foeticide techniques and pharmacological agents have been used to achieve foetal asystole. Pharmacological agents used in the foeticide procedure can be injected as intracardiac, funic, intrafetal, or intraamniotic, and the most commonly used are potassium chloride (KCl), digoxin, and lidocaine. The success rates and clinical outcomes in achieving foetal asystole are similar for intracardiac KCl, funic KCl, and intra-amniotic digoxin procedures. Foeticide with intra-amniotic digoxin is less difficult to perform, and patients experience less pain associated with the procedure. All three techniques appear to be safe and have similar short-term obstetric outcomes. Physicians may prefer foeticide with intra-amniotic digoxin as the procedure is technically simpler and has similar success rates to intracardiac or funic KCl administration. A prospective randomised study could better compare the advantages and limitations of the foeticide techniques.